Analisis Pemeringkatan Sukuk: Perspektif Keuangan - Pramesti, Wahyu (Universitas Islam Negeri Sunan Kudus, 2017)
The aims of this study is to analysed sukuk rating from financial perspective. Financial perspective used in this research is profitability, likuidity, and firm size. Sample used in this study is sukuk listed in BEI during 2010 – 2015. Used multiple regression to analysis model both partially and simultanly. Used financial performance to analyse sukuk rating. The result of this study show that profitability, likuidity, and firm size have significant effect to sukuk rating